2020
DOI: 10.1177/0954410020950511
|View full text |Cite
|
Sign up to set email alerts
|

Structural health monitoring of an adhesively bonded CFRP aircraft fuselage by ultrasonic Lamb Waves

Abstract: The aviation industry faces the challenge of offering aircraft that are lighter, more economical, and safer. One of the solutions is to increase the use of composites. For these materials, adhesive bonding has proven to be the appropriate joining technology. To check these adhesive joints, costly and time-consuming maintenance measures are carried out. An intelligent Structural Health Monitoring (SHM) system can extend these intervals and allow the use of a predictive maintenance system. This paper describes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The main 'ingredients' in composite manufacturing are carbon-fiber-reinforced polymers (CFRP) and epoxy resins [14]. CFPRs constitute an ideal material for aerospace engineering applications due to their lightweight characteristics and weight-saving outcomes and temperature-change durability [29].…”
Section: Aviation Composite Wastementioning
confidence: 99%
“…The main 'ingredients' in composite manufacturing are carbon-fiber-reinforced polymers (CFRP) and epoxy resins [14]. CFPRs constitute an ideal material for aerospace engineering applications due to their lightweight characteristics and weight-saving outcomes and temperature-change durability [29].…”
Section: Aviation Composite Wastementioning
confidence: 99%
“…Specifically for adhesive joints monitoring under the framework of LW-based SHM, PWAS have been widely used. 16,32,67,68 Since the PWAS are often bonded to the structure, their effects in the SHM monitoring system must also be considered. 69 Studies reported a shear lag effect caused by the adhesive, 70,71 more critical for lower shear modulus and thicker adhesive layers, which translated into worse shear transfer capability between the PWAS and the structure and reduced signal amplitude.…”
Section: Piezoceramic Transducersmentioning
confidence: 99%
“…Michaels and Michaels 66 also used PWAS to detect damage in‐situ by using LW. Specifically for adhesive joints monitoring under the framework of LW‐based SHM, PWAS have been widely used 16,32,67,68 …”
Section: Adhesive Jointsmentioning
confidence: 99%
“…In recent years, composite materials have been widely used in aviation, machinery, medicine, and other fields due to their excellent mechanical properties such as high strength and high ratio. The consequent problem is the need for dynamic monitoring and maintenance of composite materials in service [ 1 , 2 , 3 ]. Because composite materials are often used as laminated plates, the LVI to the structure may cause the internal delamination and fracture, and these internal damages are not easy to detect.…”
Section: Introductionmentioning
confidence: 99%